Factors and processes of natural environment contamination with substitute waters and petroleum products - Suyarko, Vasyl; Ulytskyi, Oleg; SerdіukovaOlga (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Statement of the problem determine the factors and processes of contamination of the natural environment with secondary stratum waters. The subject of the research is associated reservoir waters of oil and gas wells. The object of the study is the physical and chemical features of associated reservoir solutions containing hydrocarbons and the processes of their influence on natural ecological systems. The relevance of the research topic is determined by the danger of accompanying reservoir waters and oil products for natural ecological systems and human health. Factors and processes of pollution of the natural environment due to leaks of associated formation water (SW) and oil products in the process of search, exploration and exploitation of hydrocarbon deposits are considered. The mechanisms and ecological consequences of this phenomenon, as well as the level of danger of individual pollutant components, were analyzed. Changes in natural ecosystems as a result of the arrival of sewage sludge and petroleum products into them were studied. Measures to protect the natural environment and reduce environmental risks during drilling of oil and gas wells and development of hydrocarbon deposits are proposed. Accompanying formation waters are brines of sodium chloride solutions (brines) formed at great depths and characterized by high pressures. In the process of drilling deep wells and extracting oil and gas, sewage sludge can gush out onto the earth’s surface. This leads to salinization of soils and withdrawal of large areas of agricultural land from circulation, pollution of local water intakes, disruption of the vital activity of flora and fauna, and most importantly – to a negative effect on the human body. It is proposed to divide the types of pollution of sewage containing petroleum products into 4 groups: sodium chloride solutions; petroleum products; toxic components of sewage sludge and petroleum products; thermal pollution by thermal SW. Results. The factors of natural protection of underground water from pollution have been determined. Intensive water exchange in the infiltration zone leads to both rapid pollution and rapid purification of groundwater and non-pressurized groundwater. Underground waters that lie deeper, due to hydrodynamic pressures, push pollutants out of aquifers and remain clean. The chemical elements and compounds of hazardous waste and oil products belonging to the first, second and third classes of danger are given. The consequences of their negative impact on the human body are indicated. A conclusion was made about the need for environmental monitoring near oil and gas industries. The environmental and economic expediency of using SW as a hydro-mineral raw material for the industrial extraction of valuable chemical elements from them is emphasized.